"Who is this little girl they hired to work here?": Women's experiences of marginalizing communication in male-dominated workplaces. Issue 4 (1st October 2020) - Dorrance Hall, Elizabeth; Gettings, Patricia E.
ABSTRACT: Drawing from research on workplace incivility, marginalization, and socialization, this study explored the experiences of 41 women who self-identified as being in the early stages of careers in male-dominated workplaces. Analysis of interviews suggested a model that explicates the process of marginalization including (a) marginalizing communication (six categories that range from micro to macro-aggressions), (b) interpretation, (c) response, and (d) outcomes. Based on participants' descriptions, the model explains how societal and job contexts and personal factors (constraints, previous experience, social networks) shape the process of workplace marginalization. This study offers an integrated approach to conceptualizing marginalization as a process-based and communicative phenomenon.